2016
DOI: 10.1093/icvts/ivw321
|View full text |Cite
|
Sign up to set email alerts
|

Pooled analysis for surgical treatment for isolated adrenal metastasis and non-small cell lung cancer

Abstract: NSCLC patients with isolated adrenal metastasis undergoing surgical treatment for the primary tumour and adrenal metastasis could achieve a significant survival benefit, especially if they have metachronous adrenal metastasis or are negative for lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…LCC and lymph node metastasis are factors of poor prognosis . For patients with synchronous isolated adrenal metastatic NSCLC, the median OS after lung surgery and complete adrenalectomy was 12 months, and the five‐year survival rate was around 20% . Adrenal metastasis has more significant benefits than other oligometastasis for comprehensive treatment of combined surgery, without significant difference among various pathological types .…”
Section: Discussionmentioning
confidence: 99%
“…LCC and lymph node metastasis are factors of poor prognosis . For patients with synchronous isolated adrenal metastatic NSCLC, the median OS after lung surgery and complete adrenalectomy was 12 months, and the five‐year survival rate was around 20% . Adrenal metastasis has more significant benefits than other oligometastasis for comprehensive treatment of combined surgery, without significant difference among various pathological types .…”
Section: Discussionmentioning
confidence: 99%
“…35 Two-year OS after surgery in Gao et al's pooled analysis was 40.5%, and 5-year OS was 28.2% (n=98 patients). 48 Tanvetyanon et al described 25% 5-year OS (n=10 studies; 114 patients), 49 while Beitler et al reported approximately one-third of patients as five-year survivors.…”
Section: Discussionmentioning
confidence: 99%
“…35 Three of these four papers were restricted to surgical results in lung cancer, [48][49][50] with Gunjur and colleagues analyzing surgery (n=30 studies) and ablative RT (n=9) for adrenal OM from all primary tumor sites. 35 Gunjur et al reported a weighted 2-year OS of 46% for adrenalectomy versus 19% for SBRT, and 2-year local control (LC) of 84% versus 63% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations